Advances In Dental Bleaching Techniques - Gade, Vandana; Chaudhary, Yasmeen; Chaware, Priyanka; Rahul, Neelam; Kosare, Priya; Nikam, Tejaswini (Journal of Neonatal Surgery, 2025)
Tooth bleaching is a widely accepted esthetic procedure in dentistry aimed at addressing both intrinsic and extrinsic discoloration. Various bleaching agents, including hydrogen peroxide, carbamide peroxide, and sodium perborate, function through oxidation to break down chromogenic compounds. Techniques such as the walking bleach method, in-office power bleaching, and at-home tray bleaching have been developed to enhance whitening efficacy. Despite its benefits, bleaching may lead to complications such as enamel demineralization, tooth sensitivity, and external cervical resorption. Recent advancements, including laser-assisted bleaching, cold atmospheric plasma, and nano-filled bleaching gels, offer improved outcomes with reduced side effects. This review explores the mechanisms, techniques, complications, and innovations in bleaching, providing a comprehensive understanding of its role in endodontics.